Industrial Training Report: Perpustakaan Sultanah Nur Zahirah Universiti Malaysia Terengganu / Azirra Aziz - Aziz, Azirra (Faculty of Information Management, 2016)
Perpustakaan Sultanah Nur Zahirah (PSNZ) is an academic library placed in University malaysia terengganu (UMT). I has undergone in five months. PSNZ is one of the suitable places for me as a student to intership as it offers a lot of opportunities for practical students to learn and develop in many areas. For this intership, which is August until Disember 2016, i have gained alot of experience through tasks given. In this internship report I will describe my experiences during my internship period. The internship report contains an overview of the internship company and the activities,tasks and projects that I have worked on during my internship. Writing this report, I also will describe and reflect my learning objects and personal goals that I have gain during my internship period.